Brucellosis Seropositivity in Animals and Humans in Ethiopia: A Meta-analysis. - Getachew Tadesse (Public Library of Science (PLoS), 2016)
BACKGROUND:The objectives of this study were to assess the heterogeneities of estimates and to estimate the seroprevalence of brucellosis in animals and humans in Ethiopia. METHODS/PRINCIPAL FINDINGS:Data from 70 studies covering 75879 animals and 2223 humans were extracted. Rose Bengal Plate Test (RBPT) and Complement Fixation Test (CFT) in series were the most frequently used serological tests. A random effects model was used to calculate pooled prevalence estimates. The overall True Prevalence of brucellosis seropositivity in goats and sheep were estimated at 5.3% (95%CI = 3.5, 7.5) and 2.7% (95%CI = 1.8, 3.4), respectively, and 2.9% for each of camels and cattle. The prevalence was higher in post-pubertal than in pre-pubertal animals (OR = 3.1, 95% CI = 2.6, 3.7) and in the pastoral than in the mixed crop-livestock production system (OR = 2.8, 95%CI = 2.5, 3.2). The incidence rates of brucellosis in humans of pastoral and sedentary system origins were estimated at 160 and 28 per 100 000 person years, respectively. CONCLUSIONS:The seroprevalence of brucellosis is higher in goats than in other species. Its occurrence is evocative of its importance in the country in general and in the pastoral system in particular. Public awareness creation could reduce the transmission of Brucella spp. from animals to humans and the potential of livestock vaccination as a means of control of brucellosis needs to be assessed.